(untitled) (Journal of the College of Basic Education, 2023)
Contemporary Iraqi sculpture began to appear after the forties of the last century.It is known that this stage was characterized by many social and technical changes that directly affected theThe level of the sculptural output, in terms of level and style, since material and form are no longer withinthe traditional concept. Rather, it has become one of the characteristics of an evolving reality that is full of new materials.The strangeness sweeps the sculpture away from its classical path with new paths that are formally exciting and intellectually strange.consisting of (formal, material) relationships that relied mainly on the artist’s experience in creating works of art.Expressing his personal experience in the harmonization between these two elements in the dominant in the output of the productionNegative.The contemporary Iraqi artist has become specific in artistic expression.The spirit of the age that he lives in, in addition to the technical development that accompanies it without losing its roots.authentic art that extends over thousands of years, i.e. the balance between the cultural heritage and the spirit ofThe current era has clearly emerged through its ability to create and transform through its understandingThe problem of material and shape and achieving actual homogeneity and dissolving them in the plastic mold are these changes.It began to take its place in contemporary Iraqi sculpture after the end of the four decade of the last century.As the artist’s orientation seemed to focus on exploiting all material capabilities, taking advantage of the two factors of scarcity.Diversity in sculptural work, as well as the role of technology and its contribution to the process of artistic construction.With the help of local and imported materials, if possible, ushering in that field to usher in the era ofNew, full of excitement and aesthetic pleasure based on the ability to harmonize between the two elements of the materialAnd the shape.Understand from the foregoing that the imposition of the conditions of a certain form on a substance and the imposition of the conditions of a substance onA form is made possible (although the individual skills of the artist vary) because of the competence ofthe artist in splitting the material and pouring it into the mold of the sculptural mold, as well as the existing methods of processingthese materials and manipulate their morphological properties.